BIOCHEMICAL RESPONSES AND GENETIC EXPRESSIONS OF SYNTHETIC COMMON CARP POPULATIONS EXPOSED TO HIGH-AMMONIA REARING ENVIRONMENT - yogi Himawan; Alimuddin Alimuddin; Kukuh Nirmala; Imron Imron; Joni Haryadi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Carp is one of the leading freshwater aquaculture commodities in Indonesia. Further improvement of carp strains by the Research Institute for Fish Breeding (RIFB), Sukamandi, Indonesia, has produced a synthetic F2 carp. The strain is assembled from different strains of carps and has shown better growth and health characteristics. Considering that high environmental ammonia (HEA) has affected most carp grow-out systems, this study aimed to determine the performance of the synthetic carp populations in a high ammonia rearing environment. The treatments were rearing media of the synthetic carp seed populations added with and without (control) 200 mg/L NH4Cl arranged in three replicates. A total of 30 fish seeds/aquarium, weighed 10-15 g/fish, was used in the study. Dissolved oxygen levels were maintained above 2 mg/L using aeration. This study shows that higher tolerant carp populations had red blood cells of 232.66 ± 17.24 cells/mL, indicating a direct effect of high ammonia on red blood cell count (p<0.05). Cortisol levels of 80.90 ± 6.35 ng/mL in resistant carp indicate significant differences (p<0.05). The relative expressions of the HSP70 gene in the liver (Log10) ranged between 0.72 and 2.80. The values demonstrate that high ammonia-resistant synthetic carp have a higher relative expression ratio of the HSP70 gene than the less resistant group. This research concluded that the populations of synthetic F2 carp showed a degree of resistance against high-ammonia rearing conditions. When it is ready for aquaculture, this synthetic carp strain could be farmed in high density using intensive systems in HEA-affected artificial lakes and reservoir